2020
DOI: 10.1016/j.cub.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Representation of Taste-Related Decisions in the Gustatory Insular Cortex of Mice

Abstract: SUMMARY Research over the past decade has established the gustatory insular cortex (GC) as a model for studying howprimary sensory cortices integrate sensory,affective, and cognitive signals. This integration occurs through time-varyingpatterns of neural activity. Selective silencing of GC activity during specific temporal windows provided evidence forGC’s role in mediating taste palatability and expectation. Recent results also suggest that this areamay play a role in decision making. However, exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 39 publications
7
72
3
Order By: Relevance
“…Similar to recent work from the Fontanini group (Vincis et al, 2020), our study found that insula encoded predicted outcomes during the presentation of reward-predictive odor cues, and fired in anticipation of reward after completion of an instrumental response. Further, we showed that firing was higher for cues that predicted high-valued reward in both delay and size domains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to recent work from the Fontanini group (Vincis et al, 2020), our study found that insula encoded predicted outcomes during the presentation of reward-predictive odor cues, and fired in anticipation of reward after completion of an instrumental response. Further, we showed that firing was higher for cues that predicted high-valued reward in both delay and size domains.…”
Section: Discussionsupporting
confidence: 89%
“…Traditionally, the insula has been described as an interoceptive center (Craig, 2010, 2002; Damasio et al, 2000; Naqvi and Bechara, 2010), but is also thought to contribute to functions related to reward processing and decision-making (Burke and Tobler, 2011; Droutman et al, 2015; Mesulam and Mufson, 1982; Ongur and Price, 2000; Preuschoff et al, 2008; Rogers-Carter and Christianson, 2019). Consistent with these functions, recent work has shown that firing in insula correlates to the anticipation and delivery of both positive and negative outcomes (Guillem et al, 2010; Jo and Jung, 2016; Kusumoto-Yoshida et al, 2015; Mizoguchi et al, 2015; Moschak et al, 2018; Samuelsen et al, 2012; Vincis et al, 2020; Wittmann et al, 2020). Here, we ask if outcome-related neural correlates in insula are disrupted by chronic cocaine-self administration in rats performing a reward-guided decision-making task.…”
Section: Introductionmentioning
confidence: 71%
“…This fits with a recent primate neuroimaging study that showed strong activation of this entire region by visual cues indicating reward, as well as reward delivery 20 . Insula has long been known to be strongly connected with the neighboring gustatory cortex 34,35 . Recently, several lines of studies have demonstrated that neurons in the gustatory cortex not only engage the primary processing of gustatory inputs, but also involve multisensory integration 15,16 , as well as higher cognitive functions like decisionmaking 13,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Insula has long been known to be strongly connected with the neighboring gustatory cortex 34,35 . Recently, several lines of studies have demonstrated that neurons in the gustatory cortex not only engage the primary processing of gustatory inputs, but also involve multisensory integration 15,16 , as well as higher cognitive functions like decisionmaking 13,35 . This suggests that primate insular cortex and the neighboring gustatory cortex are strongly interconnected and form an interacting distributed network during decision making.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of the non-responsive neurons may be involved in encoding this information and participate in the perception of flavor [32,33] and the formation of associative representations triggered by anticipatory cues [20,21,26]. Moreover, GC neurons have been shown to encode cognitive variables associated with decision making [27,34].…”
Section: Multimodal Responses In Gcmentioning
confidence: 99%